High Systemic Immune-Inflammation Index and Body Mass Index Are Independent Risk Factors of the Thoracic Ossification of the Ligamentum Flavum. (13th August 2022) - Zhao, Yongzhao; Xiang, Qian; Lin, Jialiang; Jiang, Shuai; Li, Weishi
Abstract : Background . Inflammation has been considered to play an important role in the pathogenesis of the thoracic ossification of the ligamentum flavum (OLF). However, the inflammation-related risk factors of thoracic OLF have not been fully investigated to date. Methods . A total of 95 patients (48 in the OLF group and 47 in the control group) were included in this retrospective study to explore the independent risk factors of thoracic OLF. The following demographic and clinical variables were compared between the two groups: gender, age, body mass index (BMI), coexistence of hypertension or diabetes, and inflammation-related variables. Multivariate logistic regression analysis was utilized to determine the independent risk factors. Results . High systemic immune-inflammation index (SII) (≥621) (odds ratio OR = 12.16, 95% confidence interval CI = 2.95 – 50.17, p < 0.01 ) and BMI (≥25 kg/m 2 ) (OR = 9.17, 95 % CI = 3.22 – 26.08, p < 0.01 ) were independent risk factors of thoracic OLF. SII (R = 0.38, p < 0.01 ) and BMI (R = 0.46, p < 0.01 ) were positively associated with OLF score. Conclusion . High SII and BMI were the independent risk factors of thoracic OLF. Multicenter prospective studies with a large population should be conducted in the future to verify our findings.